Petrografia, Geoquímica, Análises Isotópicas (Sr, Nd) e Geocronologia Ar-Ar dos Basaltos de Tapirapuã (Tangará da Serra, Mato Grosso, Brasil) - BARROS, MÁRCIA APARECIDA DE SANT’ANA; MIZUSAKI, ANA MARIA; WESKA, RICARDO; DE BORBA, ANDRÉ; CHEMALE JR, FARID; DA COSTA, ELISON CARMO (Pesquisas em Geociências, 2006)
<!– .p text-align: justify; –> The basaltic flows from Tapirapuã Formation are exposed at Tangará da Serra region, 250 km from Cuiabá (MT) and the thickness can reach 310 meters. The basalts range from massive dark gray, with colunar disjunctions at the base to purple amygdaloidal at the top. They are generally fine-grained, however gabroics portions have been identified. In thin section the Tapirapuã basalts show subophitic texture. Chemical analyses in these rocks suggest tholeiitic compositions, within continental tectonic environment. There is an enrichment of light rare earth elements when compared to heavy rare earth elements. The studied samples have low contents of TiO2 and P2O5 being similar to low P2O5 and TiO2 group from Serra Geral Formation (Paraná Basin). Analyses of Sr and Nd isotopes show the following results: 87Sr/86Sr between 0.703 and 0.707, ∈Nd from –0.01 to + 2.32 and model ages (TDM)= (931 to 1.267 Ma). 40Ar / 39Ar geochronology of plagioclase crystals from Tapirapuã basalts presented a plateau age of 206 ± 6 Ma, in agreement with previous ages obtained from Anari and Tapirapuã sub-provinces. This result places the volcanic event at the limit of the Triassic-Jurassic periods, related to the opening of the North Atlantic.